2019
DOI: 10.1097/rhu.0000000000000779
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin 37 as a Novel Proangiogenic Factor in Juvenile Idiopathic Arthritis

Abstract: Our results demonstrate that IL-37 levels and mRNA expression were significantly increased in JIA patients, and their levels were positively correlated with disease activity and markers of angiogenesis (VEGF and VEGF receptors), suggesting that IL-37 may be correlated with angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Recent data indicated that IL-37 expression was significantly elevated in plasma, PBMCs and synovial fluid (SF) in JIA patients [ 23 ]. Consistent with the findings, our results also revealed that plasma IL-37 levels were higher in sJIA patients compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data indicated that IL-37 expression was significantly elevated in plasma, PBMCs and synovial fluid (SF) in JIA patients [ 23 ]. Consistent with the findings, our results also revealed that plasma IL-37 levels were higher in sJIA patients compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of sJIA disease activity is traditionally based on clinical observations and laboratory features, such as JADAS-27, CRP, ESR, PLT and so on [ 23 , 30 , 31 ]. We further analyzed the relationship between IL-37 expression and several laboratory values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this study report that following IL-37 treatment in a monkey chorioretinal vessel endothelial cell line (RF/6A), tube formation and branching points were increased (85.3 and 71.4%, respectively) along with cell proliferation, compared to PBS controls (47). IL-37 has been suggested to have pro-angiogenic roles similar to IL-18 in other diseases (158, 159), able to signal through the IL-18Ra.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…It has been shown that IL-37 affects the activity and phenotype of DCs and suppresses the inflammatory responses mediated by Th17 and IL-17 in RA, while failing to inhibit Th-17 cell differentiation ( 24 ). In a study involving 70 patients with juvenile idiopathic arthritis (JIA), serum/synovial IL-37 levels and IL-37 mRNA expression in PBMCs were positively associated with disease activity and angiogenesis indicators [including vascular endothelial growth factor (VEGF) and VEGF receptors] ( 56 ).…”
Section: Il-37 and Aidsmentioning
confidence: 99%